Visible‐Light‐Induced Reversible Self‐Assembly of Gold Nanorattles Using Anionic ortho‐Fluoroazobenzene (Part. Part. Syst. Charact. 11/2022). (21st November 2022) - Saito, Koichiro; McGehee, Keegan; Norikane, Yasuo
Abstract : In article number 2200123, Saito and co‐workers synthesize water‐soluble ortho‐fluoroazobenzene that can be photoisomerized by visible light. The compound enables reversible photoinduced self‐assembly of cubic gold nanorattles without the use of UV light. Their plasmonic properties can be easily tuned by green and blue light irradiation. The dispersion visually changes its color repeatedly.